Features of formation and development of the religious consciousness of the Kazakh people (Journal of Philosophy Culture and Political Science, 2018)
In article discusses the features of the formation and development of the religious consciousness of the Kazakh people. Today, religion is an integral part of a society that preserves and strengthens the state. This article briefly describes the history of the formation and development of religious movements in Kazakhstan.Also in article provides an analysis on the religious situation in the country and on the state policy in religious institutions. Based on sources in the article examines the facts of the religious situation in Kazakhstan and analyzes that in our country there are no religious conflicts in the religious culture of stability and mutual understanding develops.Key words: religious consciousness, Tengriism, shamanism, Islam.